FIRST PRESENTATION OF CARDIOVASCULAR DISEASE IN PREVIOUSLY HEALTHY INDIVIDUALS: THE MULTI-ETHNIC STUDY OF ATHEROSCLEROSIS - Jonathan Kermanshahchi, BA (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Assessment Background: The initial presentation of atherosclerotic cardiovascular disease (ASCVD) may be a severe, sometimes fatal outcome, and there is need for improved understanding and identification of ASCVD in asymptomatic individuals. Methods: Using data from 6,779 participants the Multi-Ethnic Study of Atherosclerosis (MESA) without known cardiovascular disease, we evaluated the association between traditional risk factors and coronary artery calcium (CAC) with first ASCVD event (angina, stroke, myocardial infarction [MI], or death/resuscitated cardiac arrest [RCA]) in cox proportional hazards models. Results: Overall, 1037 participants (15.3%) experienced a first ASCVD event over median follow-up of 15.8 years. The most common first presentation was death/RCA (27.7%). Those with CAC>0 were significantly more likely to present with angina than those with CAC=0 (26.% vs 13.0%, overall p<0.001). Black (35.6%) and Chinese (28.7%) individuals were more likely to present with death/RCA than White individuals (24.8%, overall p=0.011) and Black (25.7%) and Hispanic (29.3%) individuals were more likely to present with stroke than White (21.7%, p<0.001 overall) individuals. Women were more likely to present with death/RCA than men (29.8 vs 26.3%, overall p<0.001). Age, systolic blood pressure, diabetes, and smoking were significantly associated with a first presentation of death/RCA, while female sex and HDL-C were inversely associated. CAC (ln-transformed) was also significantly associated with first presentation of death/RCA (HR 1.15, 95% CI 1.10-1.22) and improved risk prediction when added to the Pooled Cohort Equations (continuous NRI 0.6081, 95% CI 0.4971-0.7141). Conclusions: In previously asymptomatic individuals, the most common initial presentation of ASCVD was death/resuscitated cardiac arrest. In addition to traditional risk factors, CAC was associated with an initial presentation of death/RCA, and improved risk prediction for death/RCA when added to traditional risk factors. These findings suggest CAC scoring may help to identify individuals at risk for death or resuscitated cardiac arrest as a first presentation of ASCVD.